REVITALIZING THE INDONESIAN POSTAL MUSEUM THROUGH EXPERIENCE SPACE ATMOSPHERE AS INTERACTIVE ELEMENT - Indiva Esa Prima; Didit Widiatmoko Suwardikun; Hanif Azhar; Yanuar Rahman; Santi Salayanti (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Museum Pos Indonesia, which was established in 1931, records the history of the development of postal services in Indonesia. However, a lack of innovation in the delivery of information has led to a decline in interest from visitors, especially the younger generation. This report discusses the museum's revitalization efforts with a focus on spatial ambience to create an interactive and educational experience. Elements such as lighting, materials, colors, and layout are arranged to build an atmosphere that supports historical understanding. This research uses a design thinking approach, through the stages of observation, interviews, problem formulation, idea development, prototyping, and testing. As a result, the museum space is divided into four thematic zones that illustrate the history of postal communication from the royal period to the digital future. Each zone is equipped with interactive media such as touch screens, video mapping, and digital simulations. This revitalization aims to make the museum more dynamic and participatory, so as to attract visitors, especially the younger generation who are accustomed to technology and visual experiences